High-resolution computed tomography to visualize human rib microstructure and explore age-related trabecular change for forensic contexts. (September 2022) - Mavroudas, Sophia R.; Dominguez, Victoria M.
Highlights: 3D analysis of age-related change in trabecular structure of human ribs can be captured with microCT. Trabecular thickness in the anterior rib shows the highest correlation with age-at-death compared to other trabecular analysis variables. Relative cortical area is more strongly correlated with age in the midshaft of the rib than in the anterior portion of the rib. Abstract: Objectives: Histological age-estimation relies on cortical bone quantification, but trabecularization of the cortex complicates reliable age estimation. This research aims to quantify and assess the role of age changes in the 3D trabecular structure of the human rib. Materials and Methods: High-resolution computed tomography was used to visualize internal rib microstructure and explore age-related trabecular change in male human ribs ranging in age from 20–95 years (Mean=55 years, SD=21.634 years). Two regions of interest (ROIs), midshaft (50%) and anterior (75%) were extracted from each scan to analyze age-related trabecular change. Dragonfly V4.1 was used to isolate cortical bone volumes of interest (VOIs) and three trabecular VOIs for each ROI; one each along the cutaneous cortex, the center of the medullary cavity, and the pleural cortex. Each trabecular VOI was analyzed for bone volume fraction (BV/TV), trabecular thickness (TbTh), trabecular spacing (TbSp), connectivity density (Conn.D), and degree of anisotropy (DA), within and between the 50 and 75% ROIs. Results and Conclusions: Overall, the cutaneous VOIs at both the 50% and 75% regions exhibited greater BV/TV, TbTh, and Conn.D when compared to the center and pleural VOIs. All results are consistent with expected biomechanical strain on human ribs. Both trabecular variables and cortical bone volume are moderately associated with age. These results show that 3D analysis of trabecular bone volume in specific regions can improve visualization or understanding of trabecular bone changes with age over traditional 2D methods.